2020
DOI: 10.1371/journal.pone.0235641
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analyses of multidrug-resistant Salmonella Indiana, Typhimurium, and Enteritidis isolates using MinION and MiSeq sequencing technologies

Abstract: We sequenced 25 isolates of phenotypically multidrug-resistant Salmonella Indiana (n = 11), Typhimurium (n = 8), and Enteritidis (n = 6) using both MinION long-read [SQK-LSK109 and flow cell (R9.4.1)] and MiSeq short-read (Nextera XT and MiSeq Reagent Kit v2) sequencing technologies to determine the advantages of each approach in terms of the characteristics of genome structure, antimicrobial resistance (AMR), virulence potential, whole-genome phylogeny, and pan-genome. The MinION reads were base-called in rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…Promising results of Hyb ASM have facilitated the annotation of clinically relevant genomic elements. Interestingly, similar conclusions using Hyb ASM have previously been drawn for assemblies from environmental samples [18,61] and clinical samples [62,63].…”
Section: Discussionsupporting
confidence: 78%
“…Promising results of Hyb ASM have facilitated the annotation of clinically relevant genomic elements. Interestingly, similar conclusions using Hyb ASM have previously been drawn for assemblies from environmental samples [18,61] and clinical samples [62,63].…”
Section: Discussionsupporting
confidence: 78%
“…Despite being of high enough quality to differentiate the strains, however, the polished genome assemblies had less accurate recovery of the cgMLST than contigs assembled using MiSeq Illumina short reads only. Another study similarly showed, for several strains of Salmonella enterica, that short read assembly followed by long read scaffolding more accurately reconstructed the genomes than either long read or short read assembly alone [10].…”
Section: Introductionmentioning
confidence: 94%
“…Here we provide the rst study we are aware of, that benchmarks the utility of integrated short and long read sequencing technologies for applied quasimetagenomic pathogen source tracking. Other studies have shown that integrating short read and long read information can reconstruct complete and accurate pathogen genome assemblies from pure culture isolates [9,10]. We sought to extend this work by testing whether we could reconstruct complete and accurate L. monocytogenes genomes from low species diversity quasimetagenomic samples.…”
Section: Introductionmentioning
confidence: 99%
“…results (Lemon et al, 2017;Sanderson et al, 2020). Studies on comparison of assemblies derived from Nanopore-only, Illumina, and hybrid assemblies have shown that the AMR prediction is comparable across all three methods (Chen et al, 2020). Recent advances in Nanopore sequencing and analysis workflows have demonstrated the utility of ONT sequencers for metagenomic analysis (Sanderson et al, 2020;Street et al, 2020).…”
Section: D95n/g/a D Dmentioning
confidence: 99%